2011
DOI: 10.1186/1746-1596-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Using a Powered Bone Marrow Biopsy System Results in Shorter Procedures, Causes Less Residual Pain to Adult Patients, and Yields Larger Specimens

Abstract: BackgroundIn recent years, a battery-powered bone marrow biopsy system was developed and cleared by the U.S. Food and Drug Administration to allow health care providers to access the bone marrow space quickly and efficiently. A multicenter randomized clinical trial was designed for adult patients to determine if the powered device had advantages over traditional manually-inserted needles in regard to length of procedure, patient pain, complications, user satisfaction, and pathological analysis of the specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
(20 reference statements)
3
41
0
Order By: Relevance
“…Bucher et al 3 showed that biopsy quality was rated ‘sufficient for diagnosis’ in both the control group and in the P-group. Berenson et al 4 and Swords et al also had similar results when comparing the two methods. In fact, a most recent retrospective study done by Lynch and colleagues showed that the manual method provides superior percentage and length of evaluable marrow 6…”
Section: Discussionmentioning
confidence: 70%
“…Bucher et al 3 showed that biopsy quality was rated ‘sufficient for diagnosis’ in both the control group and in the P-group. Berenson et al 4 and Swords et al also had similar results when comparing the two methods. In fact, a most recent retrospective study done by Lynch and colleagues showed that the manual method provides superior percentage and length of evaluable marrow 6…”
Section: Discussionmentioning
confidence: 70%
“…Textbooks and BMA guidelines rarely mention the aspiration technique, and when they do, rapid aspiration is mentioned [2,3,4]. Former studies have examined the impact that biopsy devices, operator profession and experience have on the quality of bone marrow (BM) assessment and pain [1,5,6,7,8,9,10]. To our knowledge, studies on the aspiration technique and its association with specimen quality are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] Of these eight, two were excluded 13 18 as they were abstracts of follow on published manuscripts. One additional study was excluded as it was an interim analysis of a single arm validation study.…”
Section: Included Studiesmentioning
confidence: 99%